Modelling formulae of strawberry whey drinks of prophylactic application - N. Tkachenko; P. Nekrasov; S. Vikul; Ya. Honcharuk (Harčova Nauka ì Tehnologìâ, 2017)
Expediency of the development of formulae and innovative technologies for production of prophylactic application drinks possessing antioxidant, probiotic and hepatoprotective properties with the use of the secondary dairy product – whey, as well as the domestic vegetable raw materials having a high content of bioactive substances has been substantiated. Formulation composition of the prophylactic drinks based on cheese whey, extract of Tagetes patula flowers and the berry filler “Strawberry” with the use of the response surface method has been developed. Bioactivity of the drinks and the complex quality indicator which accounts for the total influence of the bioactivity, organoleptic assessment and weight coefficients of the specified unit indicators were taken as the optimization criteria; as the independent factors that were varied in the course of the experiment, the mass fractions of the marigold flowers extract and the strawberries filler were selected. It is recommended that the mass fractions of the berry filler “Strawberry” and the extract of Tagetes patula flowers in the prophylactic drinks are set as 7 and 20 % of the finished product, accordingly. The practical mass fraction of the citric acid of 0.2 % was determined as it ensures high organoleptic characteristics of the finished drinks. Recommendations are given concerning development of innovative technologies of unfermented and fermented strawberry whey drinks of prophylactic application enriched with the extract of Tagetes patula flowers.